The Biographical Narratives of an Adolescent in Kinship Care: A Complex Post-Traumatic Stress Disorder Case Study - Grant T. Ryan (Psychotherapy and Counselling Journal of Australia)
The presence and impacts of violence, abuse, and neglect in the context of Australian children in kinship care is an ongoing concern for health services. This article reviews the post-traumatic stress disorder (PTSD) and complex post-traumatic stress disorder (C-PTSD) literature, covering diagnostic criteria, the impacts of and treatment for trauma among adolescents, and narrative exposure therapy (NET) processes and research. Using a clinical case study, the current research aimed to understand the lived biographical narratives of an adolescent in kinship care experiencing C-PTSD using NET transcription excerpts. Themes identified from the narratives include substance use, parental mental health and self-harm, parental assault, community violence, sleeping rough, and freedom. In addition, the International Trauma Questionnaire—Child and Adolescent (ITQ-CA) and the Depression Anxiety Stress Scales—Youth (DASS-Y) were used to identify clinically significant changes from pre- to post-intervention. Scores indicate a clinically significant decrease on both the ITQ-CA and the DASS-Y, providing preliminary support for the use of NET with adolescents in kinship care. Limitations and future considerations are discussed.